2005
DOI: 10.1128/jb.187.3.1188-1191.2005
|View full text |Cite
|
Sign up to set email alerts
|

Site-Directed Mutagenesis Analysis of Amino Acids Critical for Activity of the Type I Signal Peptidase of the Archaeon Methanococcus voltae

Abstract: Site-directed mutagenesis studies of the signal peptidase of the methanogenic archaeon Methanococcus voltae identified three conserved residues (Ser52, His122, and Asp148) critical for activity. The requirement for one conserved aspartic acid residue distinguishes the archaeal enzyme from both the Escherichia coli and yeast Sec11 enzymes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 9 publications
0
19
0
1
Order By: Relevance
“…Isolated bacterial membranes then served as the source of the archaeal enzyme in an in vitro signal peptidase assay, using a truncated, polyHis-tagged version of the Methanococcus voltae S-layer protein as the substrate. Site-directed mutagenesis of the Methanococcus voltae enzyme identified three conserved residues, Ser-52, His-122, and Asp-148, essential for activity (18). The finding that a second conserved Asp residue (Asp-142) was not crucial for catalytic function suggests differences in the mechanisms of the archaeal and eucaryal signal peptidases, since Asp residues found at both corresponding positions are essential for activity of the Saccharomyces cerevisiae enzyme (324).…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…Isolated bacterial membranes then served as the source of the archaeal enzyme in an in vitro signal peptidase assay, using a truncated, polyHis-tagged version of the Methanococcus voltae S-layer protein as the substrate. Site-directed mutagenesis of the Methanococcus voltae enzyme identified three conserved residues, Ser-52, His-122, and Asp-148, essential for activity (18). The finding that a second conserved Asp residue (Asp-142) was not crucial for catalytic function suggests differences in the mechanisms of the archaeal and eucaryal signal peptidases, since Asp residues found at both corresponding positions are essential for activity of the Saccharomyces cerevisiae enzyme (324).…”
mentioning
confidence: 93%
“…The findings of this multigenome study (16) are in agreement with earlier studies addressing predicted signal sequences in Methanococcus jannaschii (306) and Solfolobus solfataricus (2), although differences exist. Nonetheless, as discussed below, apparent similarities in the mechanism of archaeal and eucaryal signal peptidase action (18,100,437) suggest similarities between the cleavage site regions of signal sequences in these two domains.…”
Section: Archaeal Signal Sequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, both H. volcanii SPases contain the equivalents of Ser-90, His-145, Asp-273, and Asp-280 (E. coli numbering), residues implicated in SPase action in other organisms (6, 11, 12, 27-29, 34, 36-39). While the roles played by these residues in the H. volcanii enzymes' activity have yet to be addressed, earlier site-directed mutagenesis studies have shown that in the M. voltae enzyme, which is the only other archaeal SPase studied at the molecular level, the Ser-90, His-145, and Asp-280 equivalents are critical for activity (4). Given their overall similarity, one can ask why H. volcanii encodes two type I signal peptidases.…”
Section: Vol 188 2006mentioning
confidence: 99%
“…However, differences between the modes of action of the eukaryal and archaeal enzymes apparently exist. While the equivalents of the well-conserved Asp-273 and Asp-280 residues (E. coli numbering) are essential for the activity of the yeast enzyme (39), only the latter is essential for M. voltae SPase activity (4). The role assumed by the Asp-280 equivalent in the catalytic mechanism of the archaeal enzyme is unclear, since some Archaea do not contain this residue (4).…”
mentioning
confidence: 99%